A heat and moisture comfort sensing knitted fabric and a method of making the same

CN120245552BActive Publication Date: 2026-10-30DONGHUA UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510646478.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-20
Publication Date
2026-10-30
Estimated Expiration
2045-05-20

AI Technical Summary

Technical Problem

[0002]智能可穿戴纺织品在医疗监护、运动健康等领域的应用需求日益增长,亟需兼具热湿动态调节与生理信号监测功能的针织产品,涤纶针织物涤纶纤维强力高、快干性好,但吸湿性差,导致其作为运动面料使用时无法快速吸湿排汗,进而影响其使用

Benefits of technology

[0026]本发明的有益效果:本发明公开了一种热湿舒适性传感针织物及其制备方法,其从外到内依次为疏水传感层和亲水调温层,通过外层和内层亲疏水特性,构建润湿梯度以达到吸湿排汗效果,同时通过在亲水调温层中引入改性双壳层微胶囊发挥相变调温效果,避免在停止运动后发生失温问题,且由于改性双壳层微胶囊表面存在引入氨基聚乙二醇,含活性氨基的长分子链的存在使得改性双壳层微胶囊可以更好地固定于亲水调温层中,避免因洗涤导致的脱落,且由于改性双壳层微胶囊中内层壳为二氧化硅,外层壳为碳纳米管掺杂聚多巴胺,双壳层结构不仅减少芯材因洗涤或外力外泄的可能,且其还具有良好的导热特性,快速响应温度变化,发挥调温效果;疏水传感层通过涤纶织物聚酯纤维表面溶解凝固方法,固定碳纳米管导电填料,并在外部包裹聚吡咯,碳纳米管和聚吡咯的相互协同作用能发挥出良好的应变传感能力,且解决多次洗涤导致填料脱落影响应变传感性能的问题,且通过引入掺杂剂全氟辛基磺酸钾,进一步改善疏水传感层的疏水特性。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the technical field of functional textiles, in particular to a kind of hot and humid comfort sensing knitted fabric and its preparation method, it is from outside to inside in turn hydrophobic sensing layer and hydrophilic temperature regulating layer, it uses glue point transfer compound machine to carry out lamination with water-based polyurethane adhesive, wherein the hydrophobic sensing layer uses hydrophobic composite polyester fabric as raw material, and the hydrophilic temperature regulating layer uses single-sided hydrophilic temperature regulating polyester fabric as raw material;Wet gradient is constructed to achieve moisture absorption and perspiration effect, simultaneously, by introducing modified double-shell microcapsule, phase change temperature regulating effect is played, the problem of temperature loss after stopping movement is avoided, and by the surface dissolution and coagulation method of polyester fiber of polyester fabric, carbon nanotube conductive filler is fixed, and polypyrrole is wrapped outside, the problem that filler is detached due to multiple washing and affects strain sensing performance is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional textile technology, specifically to a thermal and moisture-sensing knitted fabric and its preparation method. Background Technology

[0002] The demand for smart wearable textiles in fields such as medical monitoring and sports health is growing, creating an urgent need for knitted products that combine dynamic temperature and humidity regulation with physiological signal monitoring. Polyester knitted fabrics have high strength and quick-drying properties, but poor moisture absorption, which prevents them from quickly wicking away sweat when used as sports fabrics, thus affecting their usability. Patent CN111267428B, "A Moisture-wicking School Uniform Fabric and Its Preparation Method," includes a moisture-wicking outer layer and a moisture-absorbing inner layer. The moisture-wicking layer uses highly hydrophilic cotton fibers as the main raw material, while the moisture-absorbing inner layer is composed of cotton fibers, polyester fibers, and linen fibers. By combining various fibers and using a printing process, moisture-wicking effects are achieved. However, the simple moisture-wicking effect cannot meet the requirements for temperature and humidity comfort. When sweat evaporates, it quickly takes away heat, which can easily lead to hypothermia after exercise stops. Patent CN104328653B, "A Method for Multifunctional Finishing of Textiles Using Graphene Oxide Derivatives," describes a method that involves immersing a fabric in an aqueous solution of graphene oxide derivatives, drying the fabric, and then reducing it to create a layer of reduced graphene oxide derivatives on the fabric surface. This allows the fabric to be used in fields such as healthcare, smart sensors, and mobile power generation. However, directly introducing conductive fillers through post-finishing methods can easily lead to the loss of these fillers after repeated washing, resulting in a decrease in strain sensing performance. Summary of the Invention

[0003] The purpose of this invention is to provide a thermal and moisture-comfort sensing knitted fabric and its preparation method. From the outside to the inside, it consists of a hydrophobic sensing layer and a hydrophilic temperature-regulating layer. By constructing a wetting gradient, it achieves moisture absorption and perspiration effect. At the same time, by introducing modified double-shell microcapsules, it exerts a phase change temperature regulation effect to avoid temperature loss after stopping exercise. Furthermore, by using a method of dissolving and solidifying on the surface of polyester fibers in polyester fabric, carbon nanotube conductive fillers are fixed, and polypyrrole is wrapped on the outside to solve the problem of filler detachment and affecting strain sensing performance due to repeated washing.

[0004] The objective of this invention can be achieved through the following technical solution: a thermal and moisture comfort sensing knitted fabric, consisting of a hydrophobic sensing layer and a hydrophilic temperature regulating layer from the outside to the inside, which is laminated using a dot transfer laminating machine with a water-based polyurethane adhesive, wherein the hydrophobic sensing layer is made of hydrophobic composite polyester fabric and the hydrophilic temperature regulating layer is made of single-sided hydrophilic temperature regulating polyester fabric.

[0005] A method for preparing a thermo-moisture comfort sensing knitted fabric includes the following steps: laminating a hydrophobic composite polyester fabric with a single-sided hydrophilic thermoregulating polyester fabric at a temperature of 100-105℃, a pressure of 3 kgf / cm², and a hot-pressing time of 12 s; wherein the side of the single-sided hydrophilic thermoregulating polyester fabric not coated with the microcapsule finishing liquid is coated with a water-based polyurethane adhesive at an adhesive application rate of 15-18 g / m². 2 After lamination, the material is baked at 130-140℃ for 1.5-2 minutes to obtain a heat and moisture comfort sensing knitted fabric.

[0006] The waterborne polyurethane adhesive is Anda Huatai AH-1701.

[0007] The hydrophobic composite polyester fabric is prepared by the following steps:

[0008] Step A1: Mix sodium dodecylbenzenesulfonate, aminated carbon nanotubes, deionized water, ethanol and phenol, and ultrasonically disperse for 30-40 min to obtain a carbon nanotube dispersion. Immerse polyester fabric in the carbon nanotube dispersion at a bath ratio of 1:50 for 8-10 min, perform padding treatment with a padding rate of 90%, and then hot press at a temperature of 105-108℃ and a pressure of 8 MPa for 3-5 min. Immerse in sodium hydroxide solution for 2-3 min, wash with deionized water, and dry to obtain a composite polyester fabric.

[0009] The ratio of sodium dodecylbenzenesulfonate, aminated carbon nanotubes, deionized water, ethanol, and phenol is 0.1-0.12 g : 0.27-0.3 g : 100-120 mL : 90-95 mL : 90-95 mL; the mass fraction of sodium hydroxide solution is 0.01%.

[0010] During the reaction, due to the presence of a phenol / ethanol system in the carbon nanotube dispersion, the polyester surface of the polyester fiber in the polyester fabric swells and partially dissolves. The dissolved polyester fiber can adhere to the aminated carbon nanotubes and be wrapped in the polyester fiber. Then, through hot pressing, the dissolved part solidifies to obtain a composite polyester fabric.

[0011] In the preparation of the composite polyester fabric, the aminated carbon nanotubes are Xianfeng Nano XFM62-1, and the polyester fabric is 70D, 80g / m². 2 Polyester knitted fabric.

[0012] Step A2: Mix pyrrole, sodium lignosulfonate and deionized water, stir at 140-180 rpm at room temperature for 15-20 min, then add potassium perfluorooctyl sulfonate and continue stirring for 15-20 min to obtain a finishing solution. Immerse the composite polyester fabric in the finishing solution at a bath ratio of 1:80, add ferric chloride, and react at 5℃ for 1.5-2 h. Wash with ethanol solution, wash with deionized water, and dry to obtain a hydrophobic composite polyester fabric.

[0013] The ratio of pyrrole, sodium lignosulfonate, deionized water, and potassium perfluorooctyl sulfonate is 6.5-6.7 g : 1-1.1 g : 100-120 mL : 1.3-1.4 g; the ethanol solution has a mass fraction of 3%.

[0014] In the reaction process, sodium lignosulfonate was used as a soft template and ferric chloride as an oxidant. Since the composite polyester fabric contains amino carbon nanotubes, the presence of amino groups promotes the in-situ polymerization of pyrrole on the surface of the composite polyester fabric. At the same time, potassium perfluorooctyl sulfonate anionic dopant was added, which electrostatically attracts the positively charged polypyrrole molecular chains and thus deposits them on the surface of the composite polyester fabric, thus obtaining a hydrophobic composite polyester fabric.

[0015] The single-sided hydrophilic temperature-regulating polyester fabric is prepared by the following steps:

[0016] Weigh the following raw materials by weight percentage: 25-28% modified double-shell microcapsules, 8-10% binder and 3.5-4% thickener, with the remainder being deionized water. Mix the modified double-shell microcapsules, binder, thickener and deionized water, and stir for 15-20 minutes at room temperature to obtain a microcapsule finishing solution. Use a doctor blade coater to coat the microcapsule finishing solution onto polyester fabric, with a single-sided coating thickness of 0.01 mm and a doctor blade coating speed of 0.4 m / min. Then pre-dry at a temperature of 75-80℃ for 8-10 minutes, and then raise the temperature to 120-125℃ and continue drying for 3-5 minutes to obtain a single-sided hydrophilic temperature-regulating polyester fabric.

[0017] In the preparation process of single-sided hydrophilic temperature-regulating polyester fabric, the adhesive is Guangdong Kefeng F-614, the thickener is Guangdong Yuemei AMS-301, and the polyester fabric is 70D, 100g / m². 2 Polyester knitted fabric.

[0018] The modified double-shell microcapsules were prepared by the following steps:

[0019] Step B1: Mix hexadecyltrimethylammonium bromide and deionized water, and stir for 15-20 min at a stirring speed of 180-240 rpm and a temperature of 65°C. Then add paraffin wax and stir for 10-15 min at a stirring speed of 8000-8500 rpm to obtain an emulsion system. Mix sodium metasilicate pentahydrate and deionized water, and stir at a stirring speed of 180-240 rpm and a temperature of 65°C. Add hydrochloric acid solution to adjust the pH to 5 to obtain a silica sol system. Add the silica sol system to the emulsion system and stir for 8-10 h at a stirring speed of 110-120 rpm and a temperature of 65°C. Filter, wash, and dry to obtain paraffin microcapsules.

[0020] In the preparation of the emulsion system, the ratio of hexadecyltrimethylammonium bromide, deionized water, and paraffin is 0.32-0.35g: 70-80mL: 4.5-5g; in the preparation of the silica sol system, the hydrochloric acid solution has a mass fraction of 35%, and the ratio of sodium metasilicate pentahydrate to deionized water is 4.5-5.2g: 50-55mL.

[0021] During the reaction, the sol-gel method was used, with deionized water as the aqueous medium. Under acidic conditions, sodium metasilicate pentahydrate was used as a silica precursor to form a silica shell on the surface of paraffin, thus producing paraffin microcapsules encapsulating paraffin with silica.

[0022] Step B2: Mix paraffin microcapsules, dopamine hydrochloride, and Tris-HCl buffer at a stirring rate of 120-140 rpm at room temperature for 2-3 hours. Then add carboxylated carbon nanotubes and continue stirring for 12 hours. Filter, wash, and dry to obtain double-shell microcapsules. Mix double-terminated amino polyethylene glycol and Tris-HCl buffer at room temperature, stir, and add the double-shell microcapsules. Sonicate for 10-15 minutes, heat to 35-40℃, and react for 10-12 hours. Filter, wash, and dry to obtain modified double-shell microcapsules.

[0023] In the preparation of double-shell microcapsules, the molar concentration of Tris-HCl buffer was 0.01 mol / L, the pH value was 8.5, and the ratio of paraffin microcapsules, dopamine hydrochloride, Tris-HCl buffer, and carboxylated carbon nanotubes was 2.8-3 g : 1.2-1.4 g : 100-110 mL : 1.8-1.9 g; in the preparation of modified double-shell microcapsules, the molar concentration of Tris-HCl buffer was 0.01 mol / L, the pH value was 8.5, and the ratio of diamino-terminated polyethylene glycol, Tris-HCl buffer, and double-shell microcapsules was 4.5-5 g : 60-70 mL : 2.3-2.5 g.

[0024] During the reaction, in Tris-HCl buffer, a shell layer with polydopamine as the shell material and carboxylated carbon nanotubes as the dopant material is formed on the surface of paraffin microcapsules to obtain double-shell microcapsules. Then, the polydopamine layer reacts with the amino groups in the double-terminated polyethylene glycol to obtain modified double-shell microcapsules.

[0025] The bi-amino-terminated polyethylene glycol is Weihua Bio's bi-amino-terminated polyethylene glycol, product number WH00503, and the carboxylated carbon nanotubes are Xianfeng Nano XFM36.

[0026] The beneficial effects of this invention: This invention discloses a thermo-moisture comfort sensing knitted fabric and its preparation method. From the outside to the inside, it consists of a hydrophobic sensing layer and a hydrophilic temperature-regulating layer. Through the hydrophilic and hydrophobic properties of the outer and inner layers, a wetting gradient is constructed to achieve moisture absorption and perspiration wicking. Simultaneously, by introducing modified double-shell microcapsules into the hydrophilic temperature-regulating layer, a phase change temperature-regulating effect is achieved, preventing temperature loss after cessation of activity. Furthermore, due to the presence of amino polyethylene glycol on the surface of the modified double-shell microcapsules, the long molecular chains containing active amino groups allow the modified double-shell microcapsules to be better fixed within the hydrophilic temperature-regulating layer, preventing them from falling off due to washing. Moreover, the modified double-shell microcapsules... The inner shell of the capsule is made of silica, and the outer shell is made of carbon nanotubes doped with polydopamine. The double-shell structure not only reduces the possibility of core material leakage due to washing or external force, but also has good thermal conductivity, responds quickly to temperature changes, and plays a temperature regulation role. The hydrophobic sensing layer fixes the carbon nanotube conductive filler by dissolving and solidifying on the surface of polyester fibers of polyester fabric, and is wrapped with polypyrrole on the outside. The synergistic effect of carbon nanotubes and polypyrrole can play a good strain sensing ability and solve the problem of filler detachment due to repeated washing affecting strain sensing performance. Furthermore, the hydrophobic properties of the hydrophobic sensing layer are further improved by introducing potassium perfluorooctyl sulfonate, a dopant. Detailed Implementation

[0027] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0028] Example 1 A thermo-moisture comfort sensing knitted fabric, consisting of a hydrophobic sensing layer and a hydrophilic temperature regulating layer from the outside to the inside, is laminated using a dot transfer laminating machine with water-based polyurethane adhesive. The hydrophobic sensing layer is made of hydrophobic composite polyester fabric, and the hydrophilic temperature regulating layer is made of single-sided hydrophilic temperature regulating polyester fabric.

[0029] A method for preparing a thermo-moisture comfort sensing knitted fabric includes the following steps: laminating a hydrophobic composite polyester fabric with a single-sided hydrophilic thermoregulating polyester fabric at a temperature of 100℃, a pressure of 3 kgf / cm², and a hot-pressing time of 12 s; wherein the side of the single-sided hydrophilic thermoregulating polyester fabric not coated with the microcapsule finishing liquid is coated with a water-based polyurethane adhesive at an application rate of 15 g / m². 2 After lamination, the material is baked at 130℃ for 1.5 minutes to obtain a heat and moisture comfort sensing knitted fabric.

[0030] The waterborne polyurethane adhesive is Anda Huatai AH-1701;

[0031] The hydrophobic composite polyester fabric is prepared by the following steps:

[0032] Step A1: Sodium dodecylbenzenesulfonate, aminated carbon nanotubes, deionized water, ethanol and phenol are mixed and ultrasonically dispersed for 30 min to obtain a carbon nanotube dispersion. Polyester fabric is immersed in the carbon nanotube dispersion at a bath ratio of 1:50 for 8 min. It is then subjected to padding treatment with a padding rate of 90%. The fabric is then hot-pressed for 3 min at a temperature of 105℃ and a pressure of 8 MPa, immersed in sodium hydroxide solution for 2 min, washed with deionized water, and dried to obtain a composite polyester fabric.

[0033] The ratio of sodium dodecylbenzenesulfonate, aminated carbon nanotubes, deionized water, ethanol, and phenol was 0.1 g: 0.27 g: 100 mL: 90 mL: 90 mL; the sodium hydroxide solution had a mass fraction of 0.01%.

[0034] In the preparation of the composite polyester fabric, the aminated carbon nanotubes are Xianfeng Nano XFM62-1, and the polyester fabric is 70D, 80g / m². 2 Polyester knitted fabric;

[0035] Step A2: Mix pyrrole, sodium lignosulfonate and deionized water, stir at 140 rpm for 15 min at room temperature, then add potassium perfluorooctyl sulfonate and continue stirring for 15 min to obtain a finishing solution. Immerse the composite polyester fabric in the finishing solution at a bath ratio of 1:80, add ferric chloride, and react at 5℃ for 1.5 h. Wash with ethanol solution, wash with deionized water, and dry to obtain a hydrophobic composite polyester fabric.

[0036] The ratio of pyrrole, sodium lignosulfonate, deionized water, and potassium perfluorooctyl sulfonate was 6.5 g: 1 g: 100 mL: 1.3 g; the ethanol solution had a mass fraction of 3%.

[0037] The single-sided hydrophilic temperature-regulating polyester fabric is prepared by the following steps:

[0038] Weigh the following raw materials by weight percentage: 28% modified double-shell microcapsules, 8% binder and 3.5% thickener, with the remainder being deionized water. Mix the modified double-shell microcapsules, binder, thickener and deionized water, and stir for 20 minutes at room temperature to obtain a microcapsule finishing solution. Use a doctor blade coater to coat the microcapsule finishing solution onto polyester fabric, with a single-sided coating thickness of 0.01 mm and a doctor blade coating speed of 0.4 m / min. Then pre-dry at 75℃ for 10 minutes, then raise the temperature to 120℃ and continue drying for 5 minutes to obtain a single-sided hydrophilic temperature-regulating polyester fabric.

[0039] In the preparation process of single-sided hydrophilic temperature-regulating polyester fabric, the adhesive is Guangdong Kefeng F-614, the thickener is Guangdong Yuemei AMS-301, and the polyester fabric is 70D, 100g / m². 2 Polyester knitted fabric;

[0040] The modified double-shell microcapsules were prepared by the following steps:

[0041] Step B1: Mix hexadecyltrimethylammonium bromide and deionized water, stir for 20 min at 180 rpm and 65°C, then add paraffin wax and stir for 10 min at 8500 rpm to obtain an emulsion system. Mix sodium metasilicate pentahydrate and deionized water, stir at 240 rpm and 65°C, and add hydrochloric acid solution to adjust the pH to 5 to obtain a silica sol system. Add the silica sol system to the emulsion system and stir for 8 h at 120 rpm and 65°C. Filter, wash, and dry to obtain paraffin microcapsules.

[0042] In the preparation of the emulsion system, the ratio of hexadecyltrimethylammonium bromide, deionized water, and paraffin was 0.35 g: 80 mL: 4.5 g; in the preparation of the silica sol system, the hydrochloric acid solution had a mass fraction of 35%, and the ratio of sodium metasilicate pentahydrate to deionized water was 4.5 g: 55 mL.

[0043] Step B2: Paraffin microcapsules, dopamine hydrochloride, and Tris-HCl buffer were mixed and stirred at 120 rpm at room temperature for 3 h. Then, carboxylated carbon nanotubes were added, and stirring was continued for 12 h. The mixture was filtered, washed, and dried to obtain double-shell microcapsules. The double-shell microcapsules were then mixed with diamino-terminated polyethylene glycol and Tris-HCl buffer, stirred at room temperature, and the mixture was added. The mixture was ultrasonically dispersed for 10 min, heated to 35 °C, and reacted for 12 h. The mixture was then filtered, washed, and dried to obtain modified double-shell microcapsules.

[0044] In the preparation of double-shell microcapsules, the molar concentration of Tris-HCl buffer was 0.01 mol / L, the pH value was 8.5, and the ratio of paraffin microcapsules, dopamine hydrochloride, Tris-HCl buffer, and carboxylated carbon nanotubes was 2.8 g: 1.2 g: 110 mL: 1.8 g; in the preparation of modified double-shell microcapsules, the molar concentration of Tris-HCl buffer was 0.01 mol / L, the pH value was 8.5, and the ratio of diamino-terminated polyethylene glycol, Tris-HCl buffer, and double-shell microcapsules was 5 g: 60 mL: 2.3 g.

[0045] The bi-amino-terminated polyethylene glycol is Weihua Bio's bi-amino-terminated polyethylene glycol, product number WH00503, and the carboxylated carbon nanotubes are Xianfeng Nano XFM36.

[0046] Example 2 A thermo-moisture comfort sensing knitted fabric, consisting of a hydrophobic sensing layer and a hydrophilic temperature regulating layer from the outside to the inside, is laminated using a dot transfer laminating machine with a water-based polyurethane adhesive. The hydrophobic sensing layer is made of hydrophobic composite polyester fabric, and the hydrophilic temperature regulating layer is made of single-sided hydrophilic temperature regulating polyester fabric.

[0047] A method for preparing a thermo-moisture comfort sensing knitted fabric includes the following steps: laminating a hydrophobic composite polyester fabric with a single-sided hydrophilic thermoregulating polyester fabric at a temperature of 105℃, a pressure of 3 kgf / cm², and a hot-pressing time of 12 s; wherein the side of the single-sided hydrophilic thermoregulating polyester fabric not coated with the microcapsule finishing liquid is coated with an aqueous polyurethane adhesive at an application rate of 15 g / m². 2 After lamination, the material is baked at 130℃ for 12 minutes to obtain a heat and moisture comfort sensing knitted fabric.

[0048] The waterborne polyurethane adhesive is Anda Huatai AH-1701;

[0049] The hydrophobic composite polyester fabric is prepared by the following steps:

[0050] Step A1: Sodium dodecylbenzenesulfonate, aminated carbon nanotubes, deionized water, ethanol and phenol are mixed and ultrasonically dispersed for 30 min to obtain a carbon nanotube dispersion. Polyester fabric is immersed in the carbon nanotube dispersion at a bath ratio of 1:50 for 10 min. It is then subjected to padding treatment with a padding rate of 90%. The fabric is then hot-pressed for 5 min at a temperature of 105℃ and a pressure of 8 MPa, immersed in sodium hydroxide solution for 2 min, washed with deionized water, and dried to obtain a composite polyester fabric.

[0051] The ratio of sodium dodecylbenzenesulfonate, aminated carbon nanotubes, deionized water, ethanol, and phenol was 0.12 g: 0.27 g: 120 mL: 90 mL: 90 mL; the sodium hydroxide solution had a mass fraction of 0.01%.

[0052] In the preparation of the composite polyester fabric, the aminated carbon nanotubes are Xianfeng Nano XFM62-1, and the polyester fabric is 70D, 80g / m². 2 Polyester knitted fabric.

[0053] Step A2: Mix pyrrole, sodium lignosulfonate and deionized water, stir for 15 min at room temperature with a stirring speed of 180 rpm, then add potassium perfluorooctyl sulfonate and continue stirring for 15 min to obtain a finishing solution. Immerse the composite polyester fabric in the finishing solution with a bath ratio of 1:80, add ferric chloride, and react for 2 h at a temperature of 5℃. Wash with ethanol solution, wash with deionized water, and dry to obtain a hydrophobic composite polyester fabric.

[0054] The ratio of pyrrole, sodium lignosulfonate, deionized water, and potassium perfluorooctyl sulfonate was 6.5 g: 1.1 g: 100 mL: 1.4 g; the ethanol solution had a mass fraction of 3%.

[0055] The single-sided hydrophilic temperature-regulating polyester fabric is prepared by the following steps:

[0056] Weigh the following raw materials by weight percentage: 25% modified double-shell microcapsules, 8% binder and 3.5% thickener, with the remainder being deionized water. Mix the modified double-shell microcapsules, binder, thickener and deionized water, and stir for 15 minutes at room temperature to obtain a microcapsule finishing solution. Use a doctor blade coater to coat the microcapsule finishing solution onto polyester fabric, with a single-sided coating thickness of 0.01 mm and a doctor blade coating speed of 0.4 m / min. Then pre-dry at 75℃ for 8 minutes, then raise the temperature to 125℃ and continue drying for 3 minutes to obtain a single-sided hydrophilic temperature-regulating polyester fabric.

[0057] In the preparation process of single-sided hydrophilic temperature-regulating polyester fabric, the adhesive is Guangdong Kefeng F-614, the thickener is Guangdong Yuemei AMS-301, and the polyester fabric is 70D, 100g / m². 2 Polyester knitted fabric;

[0058] The modified double-shell microcapsules were prepared by the following steps:

[0059] Step B1: Mix hexadecyltrimethylammonium bromide and deionized water, stir for 15 min at 180 rpm and 65°C, then add paraffin wax and stir for 10 min at 8000 rpm to obtain an emulsion system. Mix sodium metasilicate pentahydrate and deionized water, stir at 180 rpm and 65°C, and add hydrochloric acid solution to adjust the pH to 5 to obtain a silica sol system. Add the silica sol system to the emulsion system and stir for 8 h at 110 rpm and 65°C. Filter, wash, and dry to obtain paraffin microcapsules.

[0060] In the preparation of the emulsion system, the ratio of hexadecyltrimethylammonium bromide, deionized water, and paraffin was 0.32 g: 70 mL: 4.5 g; in the preparation of the silica sol system, the hydrochloric acid solution had a mass fraction of 35%, and the ratio of sodium metasilicate pentahydrate to deionized water was 4.5 g: 50 mL.

[0061] Step B2: Paraffin microcapsules, dopamine hydrochloride, and Tris-HCl buffer were mixed and stirred at 120 rpm at room temperature for 2 h. Carboxylated carbon nanotubes were then added, and stirring was continued for 12 h. The mixture was filtered, washed, and dried to obtain double-shell microcapsules. The double-shell microcapsules were then mixed with diamino-terminated polyethylene glycol and Tris-HCl buffer, stirred at room temperature, and the mixture was added. The mixture was ultrasonically dispersed for 10 min, heated to 35 °C, and reacted for 10 h. The mixture was then filtered, washed, and dried to obtain modified double-shell microcapsules.

[0062] In the preparation of double-shell microcapsules, the molar concentration of Tris-HCl buffer was 0.01 mol / L, the pH value was 8.5, and the ratio of paraffin microcapsules, dopamine hydrochloride, Tris-HCl buffer, and carboxylated carbon nanotubes was 2.8 g: 1.2 g: 100 mL: 1.8 g; in the preparation of modified double-shell microcapsules, the molar concentration of Tris-HCl buffer was 0.01 mol / L, the pH value was 8.5, and the ratio of bi-amino-terminated polyethylene glycol, Tris-HCl buffer, and double-shell microcapsules was 4.5 g: 60 mL: 2.3 g.

[0063] The bi-amino-terminated polyethylene glycol is Weihua Bio's bi-amino-terminated polyethylene glycol, product number WH00503, and the carboxylated carbon nanotubes are Xianfeng Nano XFM36.

[0064] Example 3 A thermal and moisture comfort sensing knitted fabric, consisting of a hydrophobic sensing layer and a hydrophilic temperature regulating layer from the outside to the inside, is laminated using a dot transfer laminating machine with water-based polyurethane adhesive. The hydrophobic sensing layer is made of hydrophobic composite polyester fabric, and the hydrophilic temperature regulating layer is made of single-sided hydrophilic temperature regulating polyester fabric.

[0065] A method for preparing a thermo-moisture comfort sensing knitted fabric includes the following steps: laminating a hydrophobic composite polyester fabric with a single-sided hydrophilic thermoregulating polyester fabric at a temperature of 105℃, a pressure of 3 kgf / cm², and a hot-pressing time of 12 s; wherein the side of the single-sided hydrophilic thermoregulating polyester fabric not coated with the microcapsule finishing liquid is coated with an aqueous polyurethane adhesive at an application rate of 18 g / m². 2 After lamination, the material is baked at 140℃ for 2 minutes to obtain a heat and moisture comfort sensing knitted fabric.

[0066] The waterborne polyurethane adhesive is Anda Huatai AH-1701;

[0067] The hydrophobic composite polyester fabric is prepared by the following steps:

[0068] Step A1: Sodium dodecylbenzenesulfonate, aminated carbon nanotubes, deionized water, ethanol and phenol are mixed and ultrasonically dispersed for 40 min to obtain a carbon nanotube dispersion. Polyester fabric is immersed in the carbon nanotube dispersion at a bath ratio of 1:50 for 10 min. It is then subjected to padding treatment with a padding rate of 90%. The fabric is then hot-pressed for 5 min at a temperature of 108℃ and a pressure of 8 MPa, immersed in sodium hydroxide solution for 3 min, washed with deionized water, and dried to obtain a composite polyester fabric.

[0069] The ratio of sodium dodecylbenzenesulfonate, aminated carbon nanotubes, deionized water, ethanol, and phenol was 0.12 g: 0.3 g: 120 mL: 95 mL: 95 mL; the sodium hydroxide solution had a mass fraction of 0.01%.

[0070] In the preparation of the composite polyester fabric, the aminated carbon nanotubes are Xianfeng Nano XFM62-1, and the polyester fabric is 70D, 80g / m². 2 Polyester knitted fabric;

[0071] Step A2: Mix pyrrole, sodium lignosulfonate and deionized water, stir at 180 rpm for 20 min at room temperature, then add potassium perfluorooctyl sulfonate and continue stirring for 20 min to obtain a finishing solution. Immerse the composite polyester fabric in the finishing solution at a bath ratio of 1:80, add ferric chloride, and react at 5℃ for 2 h. Wash with ethanol solution, wash with deionized water, and dry to obtain a hydrophobic composite polyester fabric.

[0072] The ratio of pyrrole, sodium lignosulfonate, deionized water, and potassium perfluorooctyl sulfonate was 6.7 g: 1.1 g: 120 mL: 1.4 g; the ethanol solution had a mass fraction of 3%.

[0073] The single-sided hydrophilic temperature-regulating polyester fabric is prepared by the following steps:

[0074] Weigh the following raw materials by weight percentage: 28% modified double-shell microcapsules, 10% binder and 4% thickener, with the remainder being deionized water. Mix the modified double-shell microcapsules, binder, thickener and deionized water, and stir for 20 minutes at room temperature to obtain a microcapsule finishing solution. Use a doctor blade coater to coat the microcapsule finishing solution onto polyester fabric, with a single-sided coating thickness of 0.01 mm and a doctor blade coating speed of 0.4 m / min. Then pre-dry at 80℃ for 10 minutes, then raise the temperature to 125℃ and continue drying for 5 minutes to obtain a single-sided hydrophilic temperature-regulating polyester fabric.

[0075] In the preparation process of single-sided hydrophilic temperature-regulating polyester fabric, the adhesive is Guangdong Kefeng F-614, the thickener is Guangdong Yuemei AMS-301, and the polyester fabric is 70D, 100g / m². 2 Polyester knitted fabric;

[0076] The modified double-shell microcapsules were prepared by the following steps:

[0077] Step B1: Mix hexadecyltrimethylammonium bromide and deionized water, stir for 20 min at 240 rpm and 65°C, then add paraffin wax and stir for 15 min at 8500 rpm to obtain an emulsion system. Mix sodium metasilicate pentahydrate and deionized water, stir at 240 rpm and 65°C, and add hydrochloric acid solution to adjust the pH to 5 to obtain a silica sol system. Add the silica sol system to the emulsion system and stir for 10 h at 120 rpm and 65°C. Filter, wash, and dry to obtain paraffin microcapsules.

[0078] In the preparation of the emulsion system, the ratio of hexadecyltrimethylammonium bromide, deionized water, and paraffin was 0.35 g: 80 mL: 5 g; in the preparation of the silica sol system, the hydrochloric acid solution had a mass fraction of 35%, and the ratio of sodium metasilicate pentahydrate to deionized water was 5.2 g: 55 mL.

[0079] Step B2: Paraffin microcapsules, dopamine hydrochloride, and Tris-HCl buffer were mixed and stirred at 140 rpm at room temperature for 3 h. Carboxylated carbon nanotubes were then added, and stirring was continued for 12 h. The mixture was filtered, washed, and dried to obtain double-shell microcapsules. The double-shell microcapsules were then mixed with diamino-terminated polyethylene glycol and Tris-HCl buffer, stirred at room temperature, and the mixture was added. The mixture was ultrasonically dispersed for 15 min, heated to 40 °C, and reacted for 12 h. The mixture was then filtered, washed, and dried to obtain modified double-shell microcapsules.

[0080] In the preparation of double-shell microcapsules, the molar concentration of Tris-HCl buffer was 0.01 mol / L, the pH value was 8.5, and the ratio of paraffin microcapsules, dopamine hydrochloride, Tris-HCl buffer, and carboxylated carbon nanotubes was 3 g: 1.4 g: 110 mL: 1.9 g; in the preparation of modified double-shell microcapsules, the molar concentration of Tris-HCl buffer was 0.01 mol / L, the pH value was 8.5, and the ratio of diamino-terminated polyethylene glycol, Tris-HCl buffer, and double-shell microcapsules was 5 g: 70 mL: 2.5 g.

[0081] The bi-amino-terminated polyethylene glycol is Weihua Bio's bi-amino-terminated polyethylene glycol, product number WH00503, and the carboxylated carbon nanotubes are Xianfeng Nano XFM36.

[0082] Comparative Example 1: Compared with Example 3, the modified double-shell microcapsules in the preparation process of the single-sided hydrophilic temperature-regulating polyester fabric in Example 3 were replaced with the paraffin microcapsules in Example 3, while the other steps were the same.

[0083] Comparative Example 2: Compared with Example 3, the hydrophobic composite polyester fabric used in the preparation process of the thermal and moisture comfort sensing knitted fabric in Example 3 was replaced with a hydrophobic polyester fabric prepared according to patent CN104328653B, "A Method for Multifunctional Finishing of Textiles Using Graphene Oxide Derivatives". The fabric used was 70D, 80g / m². 2 Polyester knitted fabric.

[0084] The thermal and moisture comfort sensing knitted fabrics prepared in Examples 1, 2, 3, Comparative Example 1, and Comparative Example 2 were used. These fabrics were cut into 1cm × 10cm samples. The conductivity of the samples was tested using a Gillette 2400 digital source meter, with a measurement length of 2cm. The samples were stretched according to GB / T 3923.1-2013, with a clamping distance of 2cm and a strain range of 30%. The resistance was also tested, and the sensing sensitivity was calculated, referring to GB / T... 21655.2-2019, liquid moisture management tests were conducted. The sample was placed on a probe with the hydrophilic temperature-regulating layer facing upwards. A 0.22 mL solution of 9 g / L sodium chloride was dropped onto the surface of the knitted fabric, and the moisture management of the upper and lower surfaces was tested over 120 seconds. The unidirectional transfer index was calculated. The thermal comfort sensing knitted fabric was cut into 5 cm × 5 cm samples. The samples were kept at 25℃ for 12 hours, then placed on a 40℃ constant-temperature heating plate with the hydrophilic temperature-regulating layer facing downwards. The surface temperature of the samples was measured every 5 seconds, and the time taken to reach 40℃ was recorded. The samples were then placed at 18℃, and the time taken to cool down to 18℃ was recorded. The samples were washed 30 times in the same manner. The conductivity, heating time, and cooling time were then tested. The results are shown in the table below.

[0085] Table 1. Detection Results of Examples

[0086] Testing items Example 1 Example 2 Example 3 Electrical conductivity (S / m) 142.8 143.1 145.7 Sensing sensitivity 16.9 17.1 17.2 Unidirectional transmission index (%) 535.3 532.9 540.4 Heating time (min) 14.58 14.17 14.67 Cooling time (min) 19.17 18.58 19.58 Conductivity after washing (S / m) 135.2 139.7 140.2 Temperature rise time after washing (min) 12.00 11.83 12.92 Cooling time after washing (min) 18.58 18.25 18.92

[0087] Table 2 Comparative Test Results

[0088] Testing items Comparative Example 1 Comparative Example 2 Electrical conductivity (S / m) 135.5 113.7 Heating time (min) 15.42 14.50 Cooling time (min) 22.58 20.08 Conductivity after washing (S / m) 122.4 87.3 Temperature rise time after washing (min) 8.83 11.92 Cooling time after washing (min) 12.42 14.17

[0089] As shown in the table, the test results indicate that, when comparing Examples 1, 2, and 3 with Comparative Examples 1 and 2, the sensing sensitivity and unidirectional transfer index of Examples 1 and 2 demonstrate that the thermal comfort sensing knitted fabric of the present invention has good strain sensing performance and moisture wicking performance. However, when compared with the comparative examples, Comparative Example 1 replaced the modified double-shell microcapsules in the preparation process of the single-sided hydrophilic temperature-regulating polyester fabric of Example 3 with the paraffin microcapsules of Example 3. Due to the lack of a carbon nanotube-doped polydopamine layer and graft modification on its surface, the thermal conductivity of its microcapsules decreased, thus failing to respond quickly to temperature changes. Comparative Example 2 replaced the hydrophobic composite polyester fabric in the preparation process of the thermal comfort sensing knitted fabric of Example 3 with a hydrophobic polyester fabric. Due to the simple finishing process, its conductivity decreased significantly after washing.

[0090] In the description of this specification, the references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0091] The above content is merely an example and illustration of the concept of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A thermal and moisture-sensing knitted fabric, characterized in that: From the outside to the inside are a hydrophobic sensing layer and a hydrophilic temperature regulating layer, which are laminated using a glue dot transfer laminating machine with water-based polyurethane adhesive. The hydrophobic sensing layer is made of hydrophobic composite polyester fabric, and the hydrophilic temperature regulating layer is made of single-sided hydrophilic temperature regulating polyester fabric. The hydrophobic composite polyester fabric is prepared by the following steps: Step A1: Mix sodium dodecylbenzenesulfonate, aminated carbon nanotubes, deionized water, ethanol and phenol, and ultrasonically disperse for 30-40 min to obtain a carbon nanotube dispersion. Immerse polyester fabric in the carbon nanotube dispersion at a bath ratio of 1:50 for 8-10 min, perform padding treatment with a padding rate of 90%, and then hot press at a temperature of 105-108℃ and a pressure of 8 MPa for 3-5 min. Immerse in sodium hydroxide solution for 2-3 min, wash with deionized water, and dry to obtain a composite polyester fabric. Step A2: Mix pyrrole, sodium lignosulfonate and deionized water, stir at 140-180 rpm at room temperature for 15-20 min, then add potassium perfluorooctyl sulfonate and continue stirring for 15-20 min to obtain a finishing solution. Immerse the composite polyester fabric in the finishing solution at a bath ratio of 1:80, add ferric chloride, and react at 5℃ for 1.5-2 h. Wash with ethanol solution, wash with deionized water, and dry to obtain a hydrophobic composite polyester fabric. The single-sided hydrophilic temperature-regulating polyester fabric is prepared by the following steps: Weigh the following raw materials by weight percentage: 25-28% modified double-shell microcapsules, 8-10% binder and 3.5-4% thickener, with the remainder being deionized water. Mix the modified double-shell microcapsules, binder, thickener and deionized water, and stir for 15-20 minutes at room temperature to obtain a microcapsule finishing solution. Use a doctor blade coater to coat the microcapsule finishing solution onto polyester fabric, with a single-sided coating thickness of 0.01 mm and a doctor blade coating speed of 0.4 m / min. Then pre-dry at a temperature of 75-80℃ for 8-10 minutes, and then raise the temperature to 120-125℃ and continue drying for 3-5 minutes to obtain a single-sided hydrophilic temperature-regulating polyester fabric. The modified double-shell microcapsules were prepared by the following steps: Step B1: Mix hexadecyltrimethylammonium bromide and deionized water, and stir for 15-20 min at a stirring speed of 180-240 rpm and a temperature of 65°C. Then add paraffin wax and stir for 10-15 min at a stirring speed of 8000-8500 rpm to obtain an emulsion system. Mix sodium metasilicate pentahydrate and deionized water, and stir at a stirring speed of 180-240 rpm and a temperature of 65°C. Add hydrochloric acid solution to adjust the pH to 5 to obtain a silica sol system. Add the silica sol system to the emulsion system and stir for 8-10 h at a stirring speed of 110-120 rpm and a temperature of 65°C. Filter, wash, and dry to obtain paraffin microcapsules. Step B2: Mix paraffin microcapsules, dopamine hydrochloride, and Tris-HCl buffer at a stirring rate of 120-140 rpm at room temperature for 2-3 hours. Then add carboxylated carbon nanotubes and continue stirring for 12 hours. Filter, wash, and dry to obtain double-shell microcapsules. Mix bi-amino-terminated polyethylene glycol and Tris-HCl buffer at room temperature, stir, and add the double-shell microcapsules. Sonicate for 10-15 minutes, heat to 35-40℃, and react for 10-12 hours. Filter, wash, and dry to obtain modified double-shell microcapsules.

2. The thermal and moisture-sensing knitted fabric according to claim 1, characterized in that: In step A1: the ratio of sodium dodecylbenzenesulfonate, aminated carbon nanotubes, deionized water, ethanol and phenol is 0.1-0.12g: 0.27-0.3g: 100-120mL: 90-95mL: 90-95mL; the mass fraction of sodium hydroxide solution is 0.01%.

3. The thermal and moisture-sensing knitted fabric according to claim 1, characterized in that: In step A2: the ratio of pyrrole, sodium lignosulfonate, deionized water and potassium perfluorooctyl sulfonate is 6.5-6.7g: 1-1.1g: 100-120mL: 1.3-1.4g; the ethanol solution has a mass fraction of 3%.

4. The thermal and moisture-sensing knitted fabric according to claim 1, characterized in that: In step B1: During the preparation of the emulsion system, the ratio of hexadecyltrimethylammonium bromide, deionized water, and paraffin is 0.32-0.35g: 70-80mL: 4.5-5g; During the preparation of the silica sol system, the hydrochloric acid solution has a mass fraction of 35%, and the ratio of sodium metasilicate pentahydrate to deionized water is 4.5-5.2g: 50-55mL.

5. The thermal and moisture-sensing knitted fabric according to claim 1, characterized in that: In step B2: During the preparation of the double-shell microcapsules, the molar concentration of Tris-HCl buffer was 0.01 mol / L, the pH was 8.5, and the ratio of paraffin microcapsules, dopamine hydrochloride, Tris-HCl buffer, and carboxylated carbon nanotubes was 2.8-3 g. 1.2-1.4g: 100-110mL: 1.8-1.9g; During the preparation of modified double-shell microcapsules, the molar concentration of Tris-HCl buffer was 0.01mol / L, the pH value was 8.5, and the ratio of double-terminated amino polyethylene glycol, Tris-HCl buffer and double-shell microcapsules was 4.5-5g: 60-70mL: 2.3-2.5g.

6. A method for preparing a thermal and moisture-sensing knitted fabric as described in claim 1, characterized in that: The process includes the following steps: At a temperature of 100-105℃, a pressure of 3 kgf / cm², and a hot-pressing time of 12 seconds, a hydrophobic composite polyester fabric is laminated with a single-sided hydrophilic temperature-regulating polyester fabric. The side of the single-sided hydrophilic temperature-regulating polyester fabric not coated with the microcapsule finishing solution is coated with a water-based polyurethane adhesive at an application rate of 15-18 g / m². 2 After lamination, the material is baked at 130-140℃ for 1.5-2 minutes to obtain a heat and moisture comfort sensing knitted fabric.

Citation Information

Patent Citations

  • A method of graphene oxide derivatives for multifunctional finishing of textiles

    CN104328653B

  • A moisture-wicking school uniform fabric and its preparation method

    CN111267428B

  • Organic / inorganic hybridization double-wall self-lubricating microcapsule, preparation method and self-lubricating composite material containing microcapsule

    CN106674748A

  • Hybrid filler-added high-strength conductive hydrogel and preparation method thereof

    CN117264235A